(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nations throughout the world are revising their national agendas and developmental strategies to better reflect the United Nations’ 2030 Sustainable Development Goals (SDGs). The term "Corporate Social Responsibility" (CSR) is often used to refer to the voluntary actions taken by businesses to aid in the social, economic, and ecological development of their communities and societies beyond the bare minimum required by law. Global issues including climate change and poverty have sparked a renewed interest in recent years in the social and environmental implications of international business (IB). Companies have a duty to their stakeholders and society as a whole to follow best practices in corporate social responsibility and sustainability as a result of globalization.